English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2007-06-28 13:42:13 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

35d + 5d^2 - 30
= 5d^2 + 35d - 30
= 5(d^2 + 7d - 6)

2007-06-28 13:46:32 · answer #1 · answered by Kemmy 6 · 0 0

Is it possible that expression could read as:-
5d ² + 35d + 30?

= 5.(d² + 7d + 6)
= 5.(d + 6).(d + 1)

2007-07-02 15:12:04 · answer #2 · answered by Como 7 · 0 0

5(d^2+7d-6) =

2007-06-28 20:47:42 · answer #3 · answered by dwinbaycity 5 · 0 0

fedest.com, questions and answers